Peranan Use-casemodeling Dalam Menilai Tingkat Efektivitas Siklus Pengeluaran (Studi Kasus CV MakmurAbadi) - Ivan Senjaya (Jurnal Akuntansi, 2018)
The change of time, technology, and competition influence indirectly to company’s environment. This makes company should to review the aspects that exist within the company, one of which is the effectiveness of the company cycle. One main function of accounting information system is processing the data into useful information for decision makers to make the cycle to be effective so that corporate goals can be achieved. Use-case modeling is one of the documentation tools in the accounting information system that can also generate information about the effectiveness of a cycle. This research used analytical descriptive method as research method with data collection techniques by interview, observation, and library research. Object of this case study of research is CV Makmur Abadi, a company in textile industry. After the research process is done, it can be concluded that the role of use-case modeling in assessing effectiveness is as a supporting role by providing guidance. Use-case can provide guidance on assessing the effectiveness of cycle especially by components in use-case such as use-case narratives and use-case dependencies diagrams. With these guidance, the process assessment of effectiveness becomes more systematic to present accurate and useful information.Keywords:Use-case Modeling, Assessment of Effectiveness Level, &Expenditure Cycle.